2021
DOI: 10.4314/tjpr.v18i6.19
|View full text |Cite
|
Sign up to set email alerts
|

Anti-asthmatic effect of laurotetanine extracted from Litsea cubeba (Lour.) Pers. root on ovalbumin-induced allergic asthma rats, and elucidation of its mechanism of action

Abstract: Purpose: To investigate the anti-asthmatic effect of laurotetanine on allergic asthma rat model. Methods: Laurotetanine was extracted from the roots of Litsea cubeba (Lour.) Pers. Asthma was induced in rats by ovalbumin injection. Laurotetanine (20, 40, or 60 mg/kg) was administered orally to the rats for 21 days. Inflammatory cells and cytokines released by T-cell subsets Th1 and Th2 in the bronchoalveolar lavage fluid were determined. Serum immunoglobulin E (IgE) and histamine, in addition to expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Regarding similar compounds that emerged from the prediction results of the three SAE-DNN models, these compounds were predicted to have interactions with COVID-19 proteins. This is supported by several literature studies showing that Hyperoside, Aloin, Rhamnetin, Laurotetanine, and Isoquercetin compounds have anti-inflammatory properties [52][53][54][56][57][58], which can help fight the hyper inflammation process in COVID-19 patients. For Garcimangosone d, its efficacy on COVID-19 or the inflammatory process in the body is not yet known.…”
Section: Herbal Compounds Predictionsupporting
confidence: 56%
“…Regarding similar compounds that emerged from the prediction results of the three SAE-DNN models, these compounds were predicted to have interactions with COVID-19 proteins. This is supported by several literature studies showing that Hyperoside, Aloin, Rhamnetin, Laurotetanine, and Isoquercetin compounds have anti-inflammatory properties [52][53][54][56][57][58], which can help fight the hyper inflammation process in COVID-19 patients. For Garcimangosone d, its efficacy on COVID-19 or the inflammatory process in the body is not yet known.…”
Section: Herbal Compounds Predictionsupporting
confidence: 56%
“…Many studies have indicated that oxidative stress (imbalance between free radicals and antioxidants), inflammation, as well as reduced immunity are implicated in asthma. However, not much is known about the in-depth pathophysiology of asthma [4,5]. The current treatment regimens involve mostly inhalation drugs such as corticosteroids, anti-IgE drugs (monoclonal IgE antibodies), β2-adrenergic agonist, antileukotrienes/cholinergic (individual or combinational therapy), in addition to bronchial thermoplasty procedure.…”
Section: Introductionmentioning
confidence: 99%